ULTRASOUND FETAL KIDNEY LENGTH FOR ASSESSMENT OF GESTATIONAL AGE - Jitesh Shah (National Journal of Medical Research, 2023)
Fetal kidney length (FKL) has recently been found to have a strong correlation with gestational age. According to the findings of these investigations, the fetal kidney length may be utilized to estimate gestational age when dates are ambiguous or when women seek ultrasound fetal biometry dating during the third trimester itself.